Synthesis of copper nanoparticles by laser ablation. Issue 1 (1st August 2022) - Antipov, A A; Putilov, A G; Osipov, A V; Shepelev, A E; Glebov, V N; Maliutin, A M
Abstract: The synthesis of copper nanoparticles using a pulsed alexandrite laser is demonstrated. The laser operated in a free generation mode with a pulse duration of about 250 μs. The copper target was placed in distilled water and glycerin. The obtained colloidal solutions were investigated by dynamic light scattering, and the deposited structures were studied by atomic force and electron microscopy. The concentration of nanoparticles depended on the power of the laser radiation, the scanning speed and the exposure time. The smallest particles size was obtained at a frequency of 5 Hz at a wavelength of 750 nm. Colloids obtained in distilled water contain copper nanoparticles, which oxidize over time.